Answer:
move the constant to the right hand of the side and change the sign
2x>-0.5-5-5
calculate the difference
2x>-6
divide both sides of the inequality by 2
x>-3
solution X>-3
By the Pythagorean Theorem:
The square of the hypotenuse (longest side) of a right triangle is equal to the sum of the side lengths squared, or mathematically:
h^2=x^2+y^2, where x and y are the side lengths and h is the length of the hypotenuse, in this case:
9.4^2=6.8^2+GF^2
GF^2=9.4^2-6.8^2
GF^2=42.12
GF=√42.12 units
GF≈6.49 units (to nearest hundredth of a unit)
Answer: x=−1 and y=4
Step-by-step explanation: